2019
DOI: 10.1182/blood.2019000518
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil-platelet interactions promote atherosclerosis and stabilize thrombosis with eosinophil extracellular traps

Abstract: This study uses genetic and pharmacologic approaches to demonstrate novel roles of eosinophils in the progression of atherosclerosis and arterial thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
112
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 71 publications
1
112
0
Order By: Relevance
“…However, their secreted granules contain factors capable of potentiating tissue damage and inflammation and proteases capable of modifying the surrounding extracellular matrix and locally deposited lipoproteins [ 90 , 91 ]. Moreover, it was shown that activated neutrophils and eosinophils form extracellular traps in the vessel wall, which are implicated in the clinical severity of the coronary lesion [ 90 , 92 ].…”
Section: The Complex Role Of Lpc In Vascular Inflammationmentioning
confidence: 99%
“…However, their secreted granules contain factors capable of potentiating tissue damage and inflammation and proteases capable of modifying the surrounding extracellular matrix and locally deposited lipoproteins [ 90 , 91 ]. Moreover, it was shown that activated neutrophils and eosinophils form extracellular traps in the vessel wall, which are implicated in the clinical severity of the coronary lesion [ 90 , 92 ].…”
Section: The Complex Role Of Lpc In Vascular Inflammationmentioning
confidence: 99%
“…Eosinophils may also contribute to the lung pathology in COVID-19 patients. In hypereosinophilic cases, the degranulation of major basic protein from eosinophils and eosinophil peroxidase causes platelet aggregation and thrombus formation [24]. Eosinophils can cause in situ thrombus formation in the lungs and veins.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils may also contribute to the lung pathology in COVID-19 patients. In hypereosinophilic cases, the degranulation of major basic protein from eosinophils and eosinophil peroxidase causes platelet aggregation and thrombus formation [22]. Eosinophils can cause in situ thrombus formation in the lungs and veins.…”
Section: Discussionmentioning
confidence: 99%